Mechanism of Resveratrol on LPS/ATP-induced pyroptosis and inflammatory response in HT29 cells - Zhao, Peizhuang; Ning, Jiajia; Huang, Jun; Huang, Xue (Autoimmunity (Chur, Switzerland), 2024)
Pyroptosis plays an important role in maintenance of intestinal homeostasis, the abnormal activation of NOD-like receptor thermal protein domain-associated protein 3 (NLRP3) inflammasome can promote the event and development of ulcerative colitis (UC). Its protective effects such as inhibiting pyroptosis in various inflammation-related diseases have been demonstrated, but whether resveratrol (RES) can also alleviate the progression of the disease by inhibiting pyroptosis in UC and the mechanism have rarely been studied. In this study, lipopolysaccharide (LPS) combined with adenosine triphosphate (ATP) was used to induce HT29 human colon cancer cells to construct an intestinal epithelial cell pyroptosis and inflammation model to investigate the anti-inflammatory effect of RES, reveal the regulatory mechanism of RES on pyroptosis, and provide a new theoretical basis for the treatment of UC. experiences, HT29 cells were dividing into control group, LPS/ATP group, RES low-dose group, RES high-dose group, NF-κB inhibitor pyrrolidine dithiocarbamate group (PDTC group), and LPS/ATP+PDTC group. The mRNA expressions of pyroptosis-related indicators such as NLRP3, apoptosis-associated speck-like protein containing CARD (ASC), Caspase-1(CASP1), IL-18, IL-1β, and inflammatory factors such as TNF-α and IL-6 were detected by qRT-PCR. The protein expressions of pyroptosis-related indicators NLRP3, ASC, CASP1, IL-18, IL-1β, NF-κB-p65 in the nucleus, and IκBα and p-IκBα in the cytoplasm were detected by Western blot. Immunofluorescence saw the distribution and expression of NLRP3, ASC and NF-κB-p65 protein in each group. The morphology and degree of pyroptosis in each group were observed by transmission electron microscope. The results showed that compared with the control group, the pyroptosis-related proteins including NLRP3, ASC, CASP1, IL-18, IL-1β, and inflammatory factors including TNF-α and IL-6 in the LPS/ATP group were increased, and LPS/ATP activated the activity of NF-κB signaling pathway. Compared with the LPS/ATP group, RES downregulated the expression of pyroptosis-related proteins and inflammatory factors in HT29 cells, and inhibited the activation of the NF-κB signaling pathway in HT29 cells pyroptosis. RES down-regulates the pyroptosis of HT29 cells induced by LPS/ATP and the expression of pyroptosis-related indicators NLRP3, ASC, CASP1, IL-18, IL-1β and inflammatory factors TNF-α and IL-6 in the inflammatory response and inhibits the occurrence of pyroptosis. The mechanism is related to the inhibition of NF-κB pathway activity.